The feminism and visual culture reader - Jones, Amelia (Routledge, 2010)
Feminism is one of the most important perspectives from which visual culture has been theorized and historicized over the past forty years. Challenging the notion of feminism as a unified discourse, this second edition of The Feminism and Visual Culture Reader assembles a wide array of writings that address art, film, architecture, popular culture, new media and other visual fields from a feminist perspective. The essays, 40% of which are new to the second edition, are informed by the authors’ deep attention to historical, geographical, and disciplinary contexts as well as by cutting edge concerns such as globalization, diasporic cultural shifts, developments in new media technologies, and intersectional identity politics. The Feminism and Visual Culture Reader combines classic texts with six specially commissioned pieces, all by leading feminist critics, historians, theorists, artists, and activists. Articles are grouped into thematic sections, each of which is introduced by the editor. Providing a framework within which to understand the shifts in feminist thinking in visual studies, as well as an overview of major feminist theories of the visual, this reader also explores how issues of race, class, nationality, and sexuality enter into debates about feminism in the field of the visual
Première publication: 2003
Keywords: 1900-1999; LGBTQIA2+; approches et analyses; arts visuels et médiatiques; cours; discipline; discours dominant; fem1000; genre; har4600; identités LGBTQIA2+; interdisciplinarité; intersectionnalité; premier cycle; périodes historiques; racialisation; sexualité; systèmes d'oppressions; thématiques; théories féministes; études culturelles

Representing the Black female subject in western art - Nelson, Charmaine (Routledge, 2010)
Nelson analyzes not only how, where, why and by whom black female subjects have been represented in Western art, but also what the social and cultural impacts of the colonial legacy of racialized Western representation have been. She poses questions about the concepts of production, the consequences of comsumption and more
Disponible en ligne: https://doi-org.proxy.bibliotheques.uqam.ca/10.4324/9780203851241 Contenu: Through an-other's eyes : white Canadian artists – Black female subjects – Racing childhood : representations of black girls in Canadian art – Slavery, portraiture, and the colonial limits of Canadian art history – The fruits of resistance : reading portrait of a Negro slave on the sly – Tying the knot : Black female slave dress in Canada – Coloured nude : fetishization, disguise, dichotomy – The "hottentot venus" in Canada : modernism, censorship, and the racial limits of female sexuality – White marble, Black bodies, and the fear of the invisible Negro : – Signifying blackness in mid-nineteenth-century neoclassical sculpture – Vénus Africaine : race, beauty, and African-ness – Allegory, race, and the four continents : Jean-Baptiste Carpeaux's les quatre parties du monde soutenant la sphere céleste – Conclusion : whiteness as collective narcissism, towards a new vision.
Keywords: afro-féminisme; approches et analyses; arts; cours; discipline; féminisme afroaméricain; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; racisme; représentation des femme*; représentation des femmes* racisées; ressource en ligne; système colonial; systèmes d'oppressions; thématiques